Avaliação da citotoxicidade e potencial antioxidante de compostos orgânicos de selênio em células endoteliais - Santos, Stephanie Figueiredo (2024)
Selenium (Se) plays a fundamental role in human and animal organisms, being essential forthe formation of selenoproteins. These selenoproteins have various functions, includingtheregulation of redox balance, playing a crucial role in antioxidant defense and impactingvarious cellular processes and metabolic pathways. Interest in seleniumcompounds has beenincreasing, mainly due to their antioxidant potential. Therefore, the aimof this studywastoevaluate the cytotoxicity, antioxidant capacity, and cytoprotective potential of syntheticcompounds containing selenium, belonging to the chemical classes diselenides andselenoesters, in endothelial cells: Diphenyl diselenide (1), p-Chlorodiaryl diselenide (2), Se-butyl-1-benzoselenate (3), Se-4-chlorophenyl selenobenzoate (4), Se-4-tolyl-selenobenzoate(5), Se-phenyl-4-chlorobenzoate (6), and Se-phenyl-selenobenzoate (7). To assess cell viability, the MTT assay was used at concentrations of 10, 100, and 400 µMof eachcompound, and the IC50 (inhibitory concentration) of each compound was calculatedbasedon the obtained results. To evaluate the antioxidant potential, the DPPH• radical scavengingassay and the ABTS•+ cationic radical scavenging assay were used at the sameconcentrations of the compounds as in the MTT assay. Induction of nitric oxide productionand quantification of reactive oxygen species (DCFH-DA) were used to determine thepro-oxidant effect. The results showed that compounds 4, 5, and 7 exhibited lower cytotoxicity, as evidenced by their IC50 values. Regarding antioxidant potential, only at the highest concentration (400 µM), all compounds showed low capacity to scavenge free radicals, suggesting that the antioxidant effect of these compounds may not be related to free radical scavenging. The prototype selenoester did not induce nitric oxide production and inducedanincrease in ROS formation at a supraphysiological concentration. These data allowustoconclude that selenocompounds alter cellular response depending on concentration, exposuretime, class, and chemical structures, and may guide future studies to better understandtheirpharmacological potential.